1999
DOI: 10.1017/s0142716499001022
|View full text |Cite
|
Sign up to set email alerts
|

Learning correspondences between letters and phonemes without explicit instruction

Abstract: Three studies examined the sources of learning by which children, very early in learning to read, formed correspondences between letters and phonemes when these were not explicitly taught in the whole language instruction they received. There were three classes of predicted knowledge sources: (a) induced sublexical relations (i.e., induction of orthographic–phonological relations from the experience of print words), (b) acrophones from letter names, and (c) transfer from spelling experience. The results of Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 32 publications
3
25
0
2
Order By: Relevance
“…We have also presented consistent evidence from other long-term residuals of childhood instruction. As was predicted, the adults with phonics, when compared with those without, had greater awareness of the phonemes of heard words, greater accuracy in graphophonemic segmentation, and greater overall accuracy for the phonics sounds of letters, although following a particular pattern among the letters that had been predicted from previous research with children (FletcherFlinn & Thompson, 2004;Thompson et al, 1999). In this predicted pattern, the adults without phonics instruction were at ceiling level in giving phonics sounds for the subset of consonant letters compatible with the letter-name acrophonic principle but, in giving phonics sounds for the other letters, were inferior to the performance of the participants with childhood phonics-especially so for the vowel letters.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…We have also presented consistent evidence from other long-term residuals of childhood instruction. As was predicted, the adults with phonics, when compared with those without, had greater awareness of the phonemes of heard words, greater accuracy in graphophonemic segmentation, and greater overall accuracy for the phonics sounds of letters, although following a particular pattern among the letters that had been predicted from previous research with children (FletcherFlinn & Thompson, 2004;Thompson et al, 1999). In this predicted pattern, the adults without phonics instruction were at ceiling level in giving phonics sounds for the subset of consonant letters compatible with the letter-name acrophonic principle but, in giving phonics sounds for the other letters, were inferior to the performance of the participants with childhood phonics-especially so for the vowel letters.…”
Section: Discussionsupporting
confidence: 64%
“…Where explicit phonics is not taught in childhood, it may seem inevitable that adult readers' knowledge of the phonics sounds for individual letters will be inferior. It has been reported, however, that children who were without explicit phonics instruction had near ceiling accuracy in giving phonics sounds for the subset of the letters b, d, j, k, p, t, v, and z, but were significantly lower in accuracy for the remaining letters (Fletcher-Flinn & Thompson, 2004;Thompson, Fletcher-Flinn, & Cottrell, 1999). It was shown that this subset of letters was that from which the children could infer the phonics sound of the letter from the initial pronunciation element (e.g., / /) of the letter name (e.g., / /) that was well known to them.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning implicit approaches of reading instruction, LNK offers the exciting potential for novice readers to discover letter-phoneme correspondences on their own. Examples of letter-phoneme correspondences self-teaching were reported in first-grade readers (Thompson et al, 1999) and spellers (Treiman, 1993), both being taught using a whole language approach. In Thompson et al (1999), five-yearold beginners receiving no formal instruction about letter sounds made use of CV letter names and printed word recognition to infer grapheme-phoneme correspondences.…”
Section: Letter Names As Precursors Of Letter Soundsmentioning
confidence: 99%
“…Children who are familiar with letter names may say that y makes the sound /wǝ/ or that w corresponds to / dǝ/, treating these letters as if their sounds were at the beginnings of their names (Ellefson, Treiman, & Kessler, 2007;Thompson, Fletcher-Flinn, & Cottrell, 1999;Treiman, Weatherston, & Berch, 1994). Additional evidence comes from children who learn letter sounds before they have mastered letter names.…”
Section: Nih Public Accessmentioning
confidence: 99%